Synergistic Effects of Transformational Leadership and Work Environment on Employee Performance in the Hospitality Industry in Manado - Helni Desty Yanice Lagarense; Merinda Pandowo; Genita Lumintang; Irvan Trang (International Journal of Management Science and Information Technology, 2026)
This study examines the synergistic effect of transformational leadership and work environment on employee performance in the hospitality industry in Manado City, focusing on Aston Manado Hotel and Roger Hotel Manado. A quantitative approach was employed using a purposive sampling technique, involving 77 permanent employees (42 from Aston Manado Hotel and 35 from Roger Hotel Manado) as respondents. Data were analyzed using multiple linear regression with SPSS 26. The findings reveal that transformational leadership has a positive and significant effect on employee performance (β = 0.451; t = 7.431; p < 0.001), while the work environment also exerts a positive and significant effect on employee performance (β = 0.343; t = 6.103; p < 0.001). Simultaneously, both variables explain 64.1% of the variance in employee performance (R² = 0.641; F = 66.03; p < 0.001). These results confirm a synergistic relationship between transformational leadership and the work environment, indicating that their combined influence on employee performance is stronger than their individual effects. The study provides practical implications for hotel management by highlighting the importance of strengthening transformational leadership competencies, particularly in inspirational motivation, individualized consideration, and employee empowerment, as transformational leadership emerged as the strongest predictor of employee performance. Hotel managers are encouraged to implement structured leadership development programs, regular coaching sessions, and performance feedback mechanisms to enhance employee engagement and productivity. Furthermore, organizations should invest in improving both the physical work environment, including workplace facilities, safety standards, and employee comfort, and the psychological work environment through effective communication, teamwork, and organizational support. Given that transformational leadership and work environment jointly explain 64.1% of employee performance variance, hotel management should adopt an integrated human resource strategy that simultaneously develops leadership quality and workplace conditions. Such initiatives can improve employee productivity, service quality, guest satisfaction, and overall organizational performance in the hospitality industry.